EFEKTIFITAS PENGGUNAAN LKS TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD N 2 BANDA SAKTI - Nurainun (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2025)
The aim of this research is to determine the innovative use of Islamic Religious Education (PAI) teaching materials in the form of Student Worksheets (LKS) which are interactive, contextual, and in accordance with the characteristics of students. LKS is intended as an alternative learning medium that not only conveys material theoretically but also encourages students to participate actively in the learning process. This innovation is due to the fact that students are still less interested in PAI subjects, which are often considered monotonous and rote-centered. The LKS development process uses a Research and Development (R&D) model which includes needs analysis, planning, product development, limited trials, revision and implementation stages. The trial results show that the LKS developed is able to increase students' understanding of Islamic concepts, strengthen religious values, and facilitate more active and enjoyable learning. It is hoped that this innovation in teaching materials will be a real contribution in improving the quality of PAI learning in schools. The results of the development show that worksheets are prepared based on student needs and contextual PAI material can increase interest and motivation for learning.